1994
DOI: 10.1159/000276634
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Malignant Tumors Detected as the Cause of Vocal Cord Paralysis

Abstract: It is well known that vocal cord paralysis is sometimes the only sign of an otherwise symptom-free malignant tumor. We report 69 cases of vocal cord paralysis caused by malignant tumor experienced at our clinic over the past 18 years. They consisted of 28 cases of thyroid cancer, 21 lung cancer, 14 esophageal cancer, 3 mediastinal tumors and 3 tumors of miscellaneous origin: 41 cases were male and 28 female. In the 65 patients with unilateral paralysis, the left side was affected in 45 and the right in 20. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 9 publications
4
17
1
1
Order By: Relevance
“…VCP has been reported to be about 1.4-2.5 times more frequent on the left side than on the right 3. In our cases diagnosed with a thoracic disease, left-side VCP was 1.75 times more frequent than right-side VCP.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations
“…VCP has been reported to be about 1.4-2.5 times more frequent on the left side than on the right 3. In our cases diagnosed with a thoracic disease, left-side VCP was 1.75 times more frequent than right-side VCP.…”
Section: Discussionmentioning
confidence: 42%
“…The other three were associated with right-side paralysis, and the CT scan detected one case of right apical lung carcinoma and two cases of metastatic nodes in the right upper paratracheal region. Masaki, et al suggested that neck ultrasonography and chest X-rays were a sufficient evaluation modality for patients with right VCP 3. But in our study, CT was needed in a patient with a small right apical lung carcinoma that was hidden behind rib shadows, and also in a patient with VCP caused by phlebitis and right upper mediastinitis during use of an intravenous chemo port (an implantable port for chemotherapy).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…As controvérsias iniciam-se pela caracterização das diferentes posições assumidas pela PVP. De acordo com a posição assumida, estas podem ser classificadas em mediana, para-mediana, intermediária e em abdução completa ou cadavérica 17 . Esta é uma descrição clássica, rotineiramente empregada na clínica médica.…”
Section: Introductionunclassified